Reconfigurable Intelligent Surface Aided Generalized Spatial Modulation Based Multiuser MmWave MISO Systems - Hu, Chia-Chang; Yang, Te-Yu; Liao, Po-Kuan; Yang, Yun-An (IEEE Global Conference on Consumer Electronics, 2024)
The joint design of transmit hybrid precoding and reconfigurable intelligent surface (RIS) beamforming is studied for the generalized spatial modulation (GenSM) aided millimeter-wave (mmWave) multiuser multiple-input single-output (MU-MISO) systems. An innovative integration of the GenSM mechanism and the switch-and-inverter (SI) analog processing network is explored at the transmitter to alleviate the need of hardware complexity and energy consumption, and a coordinate update algorithm (CUA) is used to conduct antenna selection (AS) assignment. By means of relaxing RIS power consumption, only a limited number of RIS reflecting components are activated to achieve exceptional energy efficiency (EE) performance. In particular, the cross-entropy optimization (CEO) based algorithm is dedicated to optimize the unit selection and reflect beamforming at the RIS panel. Finally, simulation results confirm that the proposed GenSM-aided SIAS mmWave MU-MISO downlink system in the presence of an RIS is capable of offering an enhanced improvement on the EE.